Male partner circumcision associated with lower Trichomonas vaginalis incidence among pregnant and postpartum Kenyan women: a prospective cohort study. (12th August 2016) - Pintye, Jillian; Drake, Alison L; Unger, Jennifer A; Matemo, Daniel; Kinuthia, John; McClelland, R Scott; John-Stewart, Grace
Abstract : Objective: Trichomonas vaginalis is the world's most common curable STI and has implications for reproductive health in women. We determined incidence and correlates of T. vaginalis in an HIV-uninfected peripartum cohort. Methods: Women participating in a prospective study of peripartum HIV acquisition in Western Kenya were enrolled during pregnancy and followed until 9 months post partum. T. vaginalis was assessed every 1–3 months using wet mount microscopy. Correlates of incident T. vaginalis were determined using Cox proportional hazards models. Results: Among 1271 women enrolled, median age was 22 years (IQR 19–27) and gestational age was 22 weeks (IQR 18–26); most (78%) were married and had uncircumcised male partners (69%). Prevalent T. vaginalis was detected in 81 women (6%) at enrolment. Among women without T. vaginalis at enrolment, 112 had T. vaginalis detected during 1079 person-years of follow-up (10.4 per 100 person-years). After adjustment for socio-economic factors, male partner circumcision status, pregnancy status and other STIs, T. vaginalis incidence was higher during pregnancy than post partum (22.3 vs 7.7 per 100 person-years, adjusted HR (aHR) 3.68, 95% CI 1.90 to 7.15, p<0.001). Women with circumcised male partners had a 58% lower risk of incident T. vaginalis compared with women with uncircumcised partners (aHR 0.42, 95% CI 0.23 to 0.76, p=0.004). Employed women had lower risk of incident T. vaginalis than unemployed women (aHR 0.49, 95% CI 0.31 to 0.79, p=0.003); recent STI was associated with increased T. vaginalis risk (aHR 2.97, 95% CI 1.49 to 5.94, p=0.002). Conclusions: T. vaginalis was relatively common in this peripartum cohort. Male circumcision may confer benefits in preventing T. vaginalis .